O discurso sobre o voluntariado na Universidade do Vale do Rio dos Sinos - Unisinos - Bavaresco, Rosa Maria Serra (Universidade do Vale do Rio do Sinos, 2003)
This study aimed at presenting the discourse concerning voluntarism in the University do Vale do Rio dos Sinos – UNISINOS. The text searches from the theoriesof action, to understand the relations that are established between suject and subjectivity as well as the implications for a solidary action. Documents and interviens were used in the research aiming at clarifying the study question. The study indicated to a plurality of orientations in the discourses, a natural result that characterizes a University. Staring from de carried out analysis we elaborated propositions with the goal to build an understanding about voluntarism.
Keywords: Solidariedade; Subjetividade; Sujeito; Voluntariado; Ação; Voluntariado; Subjetividade; Solidariedade; solidarity; subject; subjectivity; voluntarism; action; Ciências Sociais Aplicadas